THU0228 Efficacy Comparison with Tocilizumab, Interleukin-1 Inhibitors and Etanercept for Treatment of Systemic Juvenile Idiopathic Arthritis. (15th July 2016) - Horneff, G.; Schultz, A.C.; Hospach, A.; Ganser, G.; Foeldvari, I.; Thon, A.; Trauzeddel, R.; Weller, F.; Minden, K.; Haas, J.P.
Abstract : Background: Since the approval of first biologics for JIA, such treatments in Germany are monitored prospectively by the BiKER registry. Methods: sJIA pts documented in BIKER exposed to Etanercept (ETA), Tocilizumab (TOC) or IL-1inhibitors were identified. A 6-month therapy period was chosen as a meaningful time for early efficacy judgement. Intention to treat analysis (ITT) of JADAS10 was performed. Discontinuation due to inefficacy/intolerance was calculated as non-response. Results: 205 sJIA patients (51% male) received 269 treatment courses with biologics (TOC 71, Anakina 36, Canakinumab 19, ETA 143). Median age and disease duration (ETA 3.3;TOC 3.3;IL-1i 3.0) were comparable. The choice of drug was influenced by the availability. ETA was started in 80% of pts before 2008 while in the TOC cohort all pts and in the IL-1i cohort 74% started therapy after 2008. Pre-treatment consisted of steroids in all pts, MTX in the ETA/TOC/IL-1i cohort in 88%/83%/76% and biologics preexposure was used in 2%/66%/86%. Concomitant treatment with systemic steroids was significantly less frequent with TOC (44%, p<0, 001) and IL-1i (44%, p<0.001) compared to 83% with ETA. Concomitant MTX was used with ETA in 81% but significantly less frequent with TOC (64%; p=0.004) or IL-1i (44%; p<0.0001). Also other DMARDs were used less frequently with TOC (9%) and IL-1i (4%) compared to ETA (24%). Systemic manifestations were present at baseline in: 8% ETA, 96% TOC and 38% IL-1i cohort. The mean±SD baseline JADAS was higher in the ETA cohort (20.7±9.1) than in the TOC cohort (16.2±10.6) or IL-1i cohort (7.8±8.9). At month 6, a marked decrease of the JADAS was noted in all cohorts. ITT analysis revealed a significant advantage of TOC and Il-1i over ETA (table). Significantly more pts reached a JADAS-Remission (JADAS≤1) upon TOC (OR/95CI 3.85/1.68–8.83/p<0.001) or upon IL-1i (OR/95CI 4.55/1.92–10.77/p=0.003) than with ETA. Significantly more pts reached a JADAS-MDA (JADAS≤3.8) upon TOC (OR 3.55/1.49–8.46/p=0.003) or upon IL-1i (OR 4.5/1.87–10.84/p<0.0001) than with ETA. ETA was more often discontinued due to inefficacy before month 6 than TOC or IL-1i. Conclusions: A high proportion of pts showed a significant response to treatment especially with TOC or with IL-1i. After 6 months on treatment JADAS remission criteria were reached by up to 50% of patients while 60% to 65% reached JADAS minimal disease activity desoite much less steroids and DMARD used with TOC or IL-1i. ETA has been used in earlier times but it is less effective and it's use in sJIA has markedly decreased in Germany. Disclosure of Interest: None declared